Pengaruh Kepemimpinan dan Motivasi Kerja terhadap Kualitas Pelayanan Publik Kecamatan Cihampelas Bandung Barat - Nesa, Putri; Hidayat, Asep Iwa; Saepudin, Aep (Universitas Batanghari Jambi, 2024)
This study aims to find out and analyze the influence of leadership and employee motivation on the quality of public services that the community receives in Cihampelas District, West Bandung Regency. The technique when taking samples in this study used a census technique, this was due to the fact that all populations were included in the sample, namely 32 employees who worked at the Cihampelas District Office, West Bandung Regency. The data obtained is based on the results of the questionnaires distributed. The SPSS application is used as an analytical method in carrying out the multiple linear regression process. This study shows the results that leadership and work motivation have a positive and significant influence on the quality of services performed by employees. The coefficient of determination (R2) in this study is 21.9% which means that leadership and employee motivation have an influence on the quality of public services. In addition, it is also known that the leadership variable is the dominant variable in influencing the quality of public services.